A Novel Three-Dimensional Vector Analysis of Axial Globe Position in Thyroid Eye Disease - Jie Guo; Jiang Qian; Yifei Yuan; Rui Zhang; Wenhu Huang (Journal of Ophthalmology)
Purpose. To define a three-dimensional (3D) vector method to describe the axial globe position in thyroid eye disease (TED). Methods. CT data from 59 patients with TED were collected and 3D images were reconstructed. A reference coordinate system was established, and the coordinates of the corneal apex and the eyeball center were calculated to obtain the globe vector EC→. The measurement reliability was evaluated. The parameters of EC→ were analyzed and compared with the results of two-dimensional (2D) CT measurement, Hertel exophthalmometry, and strabismus tests. Results. The reliability of EC→ measurement was excellent. The difference between EC→ and 2D CT measurement was significant (p=0.003), and EC→ was more consistent with Hertel exophthalmometry than with 2D CT measurement (p<0.001). There was no significant difference between EC→ and Hirschberg test, and a strong correlation was found between EC→ and synoptophore test. When one eye had a larger deviation angle than its fellow, its corneal apex shifted in the corresponding direction, but the shift of the eyeball center was not significant. The parameters of EC→ were almost perfectly consistent with the geometrical equation. Conclusions. The establishment of a 3D globe vector is feasible and reliable, and it could provide more information in the axial globe position.